Service Learning Program In Giant Bee, Malaka-Malaysia - Sri Kurnia; Imran Ilyas; Tubel Agusven; Luqman Hakim; Ruwaida Ruwaida; Alex Zami (International Journal of Community Engagement and Development, 2024)
Giant Bee Gallery is one of the galleries that can be visited by tourists in Malacca, Malaysia. Giant Bee was founded in 1978 by Mr Ong Kang Peng. The aim of establishing the Giant Bee Gallery is that apart from selling various types of honey, the Giant Bee Gallery also aims to spread knowledge to visitors about bees and their habitat. This service activity was carried out on October 31 2023 and was attended by a service team of 14 students along with 2 accompanying lecturers. The method of implementing this service activity is carried out through several stages, namely initial and preparatory activities, implementation of activities, and evaluation of activities. The result of this service activity is that the service team was able to learn a lot about bees and beekeeping and buy several delicious and healthy honey products. The types of honey in Giant Bee consist of royal jelly, propolis, bee venom honey, pupa, pollen, bee's wax, trigona honey, super honey, apple vinegar honey. Each of the 9 honeys has its own benefits.